Connecting MicroRNA and autophagy disturbances in Amyotrophic Lateral Sclerosis (ALS) - Foggin, Sophie (2022)
Growing evidence implicates miRNA dysregulation as a hallmark of Amyotrophic Lateral Sclerosis (ALS) and there has been increasing interest in their potential as biomarkers of disease. However, no miRNA biomarker signature is currently clinically available. In Chapter 3, we perform a systematic literature review to collate 727 miRNAs reported as dysregulated between ALS patients and controls across 27 studies and note overlap of many miRNAs. However, the number of ALS-relevant predicted gene targets does not correlate with miRNAs reported as more frequently dysregulated in ALS compared to randomly chosen miRNAs, not dysregulated in ALS. We establish a pipeline to identify a candidate miRNA, miR-340-5p, dysregulated in ALS and implicated in autophagy, a biochemical pathway relevant to ALS. In addition, miR-340 is known to regulate NRF2, a transcription factor which mediates antioxidant signalling, a process defective in ALS.